High-Fat Diet Affects Heavy Metal Accumulation and Toxicity to Mice Liver and Kidney Probably via Gut Microbiota - Liu, Ting; Liang, Xue; Lei, Chao; Huang, Qinhong; Song, Weiqi; Fang, Rong; Li, Chen; Li, Xiaomei; Mo, Hui; Sun, Ning; Lv, Haoran; Liu, Zhihua (Frontiers in Microbiology, 2020)
Previous studies proved that heavy metals could increase the risk of disease by acting on the gut microbiota. Meanwhile, gut microbiota played important roles in detoxifying heavy metals. However, response of gut microbiota to heavy metals and which microbes dominated this detoxification processes were still unclear. This study investigated the difference of high fat diet (HFD) and normal diet (ND) gut microbiota, their response to and detoxification effects on arsenic (As), cadmium (Cd)and lead (Pb) exposure. Results showed that gut microbiota of ND and HFD was significantly different, and responded to As, Pb and Cd exposure differently, too. When exposed to 100ppm As, Cd or Pb, HFD-fed mice accumulated more heavy metals in liver and kidney along with more severe functional damage than ND-fed mice, indicated by more dramatic increase of alanine aminotransferase (ALT), aspartate aminotransferase (AST) activities, urinary total protein (TPU), urinary uric acid (UUA) and urinary creatinine (Ucrea) content. Among ND gut microbiota, relative abundance of Bacteroides, Lactobacillus, Butyricimonas and Dorea were significantly increased by Arsenic (As) exposure; relative abundance of Faecoccus and Lactobacillus were significantly increased by Cd exposure; relative abundance of Desulfovibrio, Plasmodium and Roseburia were significantly increased by Pb exposure. However, among HFD gut microbiota, those microbes were not significantly changed. Bivariate association analysis found week positive correlations between content of fecal excreted heavy metals and richness of total fecal microbiota as well as abundance of some of the heavy metal enriched microbes. Our study concluded that HFD increased disease risk of heavy metal exposure probably via its gut microbiota which excreted less heavy metal through fecal.